Probing inefficiencies in the supply chain of falcata in Compostela Valley - Camay, Jyd L. (2016)
Timber production in the Philippines has become profitable as a result of reduced supply from extensive deforestation and increasing demand, because of this economic opportunity, farmers seized it by planting fast growing tress like falcate. Falcata can be used as raw materials for paper, ply wood, and furniture. Compostela Valley is the major producer of Falcata in Region 11. By clearly mapping out the supply chain of falcate and assessing its performance by analyzing lead time, governance and value creation and investment decision, this study identified the inefficiencies that exists in the supply chain of falcate in Compostela Valley. It has found out that farmers lacks the knowledge on crop management and marketing, there is a increasing demand but inadequate supply, logistic issue affecting the lead time of falcate, high marketing costs especially for relaying, hauling and transporting falcata logs. This study also found out that farmers can yield a higher profit if they can directly market their produce to processors if only they have a capital to do so. With these inefficiencies, the study recommends some areas for improvement such as; increase farmer?s knowledge on crop production and management, government intervention for farm to market roads, improve falcata production and reduce associated cost in marketing falcata by improving logistic operations. It is also recommended for farmers to collaborate with others farmers when marketing falcata logs to lessen the cost.